2013
DOI: 10.5812/hepatmon.11168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis D Virus Infection Among Patients With Chronic Hepatitis B Attending Birjand Hepatitis Clinic (East of Iran) in 2012

Abstract: BackgroundHepatitis delta virus (HDV) is a defective RNA virus dependent on Hepatitis B virus (HBV) infection for its replication and expression. All patients with HBV infection should be tested for the presence of HDV infection. It is estimated that approximately 5% of hepatitis B surface antigen (HbsAg) carriers in the world are HDV infected patients. HBV-HDV co-infection may lead to more severe acute disease and higher risks of fulminant hepatitis, cirrhosis, and hepatocellular carcinoma than those having H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The prevalence of HDV in the present study was similar to reported prevalence in a meta-analysis in Iran, 22 Isfahan (2.9%) 23 and Qom (2%). 13 However, it is lower than the reported prevalence rate in Hamadan (17.3%), 9 Ahvaz (11.5%), 24 Birjand (3.1%), 25 and Tabriz and Tehran (9.3%). 17 The observed difference in the prevalence of HDV infection may be attributable to the differences in the age distribution of studied population, sampling source, geographical region and time of the study.…”
Section: Discussionmentioning
confidence: 76%
“…The prevalence of HDV in the present study was similar to reported prevalence in a meta-analysis in Iran, 22 Isfahan (2.9%) 23 and Qom (2%). 13 However, it is lower than the reported prevalence rate in Hamadan (17.3%), 9 Ahvaz (11.5%), 24 Birjand (3.1%), 25 and Tabriz and Tehran (9.3%). 17 The observed difference in the prevalence of HDV infection may be attributable to the differences in the age distribution of studied population, sampling source, geographical region and time of the study.…”
Section: Discussionmentioning
confidence: 76%
“…Similar findings were reported before by Reinheimer et al [2012] as well as Gish et al [2013] which may be due to increased risk factors for viral acquisition among them. Delta infection was more common in the fourth decade of life as supported by Ziaee and Azarkar [2013], whose patients were in fourth decade as well and Zaidi et al [2010] who reported patients in fifth decade.…”
Section: Discussionmentioning
confidence: 90%
“…Ziaee et al determined the prevalence of HDV infection among chronic hepatitis B in Birjand and there was an HDV infection rate of 3.1% (26). A long-term protection against HBV for more than 20 years was illustrated by Saffar et al among neonates, who were immunized against HBV and it was very effective in decreasing chronic HBV infection prevalence in young adults, who were vaccinated in Iran.…”
Section: Discussionmentioning
confidence: 99%